Template‐Directed Solidification of Eutectic Optical Materials. Issue 11 (30th March 2018) - Kulkarni, Ashish A.; Kohanek, Julia; Tyler, Kaitlin I.; Hanson, Erik; Kim, Dong‐Uk; Thornton, Katsuyo; Braun, Paul V.
Abstract: Mesostructured materials can exhibit enhanced light–matter interactions, which can become particularly strong when the characteristic dimensions of the structure are similar to or smaller than the wavelength of light. For controlling visible to near‐infrared wavelengths, the small characteristic dimensions of the required structures usually demand fabrication by sophisticated lithographic techniques. However, these fabrication methods are restricted to producing 2D and a limited range of 3D structures. When a large volume of structured material is required, the primary approach is to use self‐assembly, and the literature includes many examples of mesostructured optical materials formed via self‐assembly. However, self‐organized materials almost always contain structural imperfections which limit their performance. Emerging work, however, is showing that by performing self‐assembly within a guiding template, the defect density in self‐assembled structures can be reduced. Particularly interesting is the possibility that utilizing a template can result in the formation of mesostructures not present in either the template or the native self‐organizing material. In this review, particular emphasis is placed on emerging results showing the effect of mesoscale templates on the microstructure of solidifying eutectic materials, with a specific focus on how template‐directed solidification may be a powerful approach for fabricating optically active structures, including optical metamaterials. Abstract : Template‐directed assembly gives access to structures that are not present in either the template or the native self‐organizing material. Proof‐of‐concept works on template‐directed self‐organization of solidifying eutectic materials have exhibited intriguing results for photonics and optical metamaterials. This article provides a review of the challenges and opportunities of this technique for forming optically powerful structures.